Efficient composite filler for water treatment and preparation method thereof
By treating the filler base material into two sides of AB with different hydrophilic properties and preparing through ultrasonic cleaning and heat treatment steps, the existing water treatment filler preparation methods and low efficiency of single hydrophilic filler are solved, and the preparation of high-efficiency composite filler is achieved, which significantly improves the separation and mass transfer efficiency.
Patent Information
- Application Number
- CN202411943379.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-04
AI Technical Summary
The existing water treatment filler preparation methods are cumbersome and focus only on a single hydrophilic filler, making it difficult to improve the processing flux and efficiency of the filler.
Two substrates of different properties are combined into a composite material to form a super-hydrophilic A-side and a hydrophobic B-side. High-efficiency composite fillers are prepared through ultrasonic cleaning and heat treatment steps.
Through alternate arrangement of AB surfaces and sonication, the separation efficiency and mass transfer efficiency of the filler are significantly improved, the preparation process is simplified, and the preparation efficiency is improved.
Smart Images

Figure CN119551746A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of water treatment, and in particular to a high-efficiency composite filler for water treatment and a preparation method thereof. Background Art
[0002] As a medium for mass transfer and separation, packing plays an extremely critical role in separation equipment. The structure, properties, material and surface characteristics of the packing all affect the fluid mechanics of the gas-liquid fluid on its surface, which further affects the efficiency of mass transfer and separation. Therefore, it is particularly important to study and optimize the processing flux and efficiency of the packing and improve the comprehensive performance of the packing.
[0003] At present, the research and application of fillers for water treatment only focus on single hydrophilic fillers, and the preparation methods of the existing technology are relatively complicated and have many shortcomings. Summary of the invention
[0004] The purpose of the present invention is to provide a high-efficiency composite filler for water treatment and a preparation method thereof, wherein the filler substrate is treated so that two sides of the filler substrate have different surface characteristics.
[0005] To achieve the above object, the present invention provides the following technical solutions: A high-efficiency composite filler for water treatment. The filler is a composite material formed by combining two base materials with different properties to form two sides A and B with different properties. The A side has super strong hydrophilicity, and the B side has weaker hydrophilicity than the A side.
[0006] Furthermore, the filler substrate surface A is made of phosphor bronze, copper, brass or copper alloy; the filler substrate surface B is made of a different type of metal or plastic than the surface A.
[0007] Furthermore, the filler substrate is a wire mesh, a thin plate, a mesh or a combination thereof; the wire mesh has a wire diameter of 0.005-5 mm and a mesh size of 10-200 meshes; the thin plate has a thickness of 0.01-5 mm; and the mesh has a hole diameter of 0.05-20 mm.
[0008] Furthermore, the filler is a structured filler such as a wire mesh corrugated filler, a plate corrugated filler, a wire mesh plate combined corrugated filler, a mesh corrugated filler, or a random filler such as a ball ring, a step ring, a Raschig ring, or a theta ring; the specific surface area of the filler is 50 to 2000 m 2 / m 3 , the porosity is 65~99.5%.
[0009] A method for preparing a high-efficiency composite filler for water treatment comprises the following steps: Step S1: placing the filler in an alkaline degreasing agent mixture and using ultrasonic cleaning; Step S2: The filler is placed in deionized water, ultrasonically cleaned and dried; Step S3: preparing an aqueous solution of a mixture of A and B, circulating the solution internally and heating the mixed solution to raise the temperature, and after reaching a certain temperature, placing the filler in the mixed solution and performing ultrasonic treatment; Step S4: The treated filler is placed in deionized water, cleaned by ultrasonic cleaning and dried.
[0010] Furthermore, the substance A is one or more combinations of sodium hydroxide, potassium hydroxide, and lithium hydroxide, and the substance B is one or more combinations of potassium peroxymonosulfonate, sodium percarbonate, potassium percarbonate, potassium hypochlorite, and sodium hypochlorite.
[0011] Furthermore, the concentration of substance A in the mixed solution is 0.5-12 mol / L, and the concentration of substance B is 0.2-16 mol / L.
[0012] Furthermore, the treatment heating temperature is 25~100°C.
[0013] Furthermore, the filler treatment time is 0.5 to 5.0 hours.
[0014] The high-efficiency composite filler for water treatment and the preparation method thereof described in the present invention have the following beneficial effects: The base material of the filler is formed into two surfaces AB with different hydrophilicity and hydrophobicity, and the surfaces AB are arranged alternately in the filler. When the gas-liquid fluid passes through the filler in countercurrent, the B surface can fully diffuse the liquid, enhance the turbulence of the gas-liquid flow, and improve the separation efficiency of the filler. The liquid that has turbulently diffused through the B surface is spread on the A surface. The strong hydrophilicity of the A surface allows the liquid to be fully spread, increasing the wettability of the filler, making the gas-liquid contact more complete, and improving the separation efficiency of the filler. The high-efficiency composite filler for water treatment described in the present invention cleverly utilizes the micro-motion of the fluid, fully integrates the reasonable combination of gas-liquid turbulence and gas-liquid contact area, and significantly improves the mass transfer efficiency of the filler. Compared with the existing filler preparation and processing technology, the preparation method of the high-efficiency composite filler for water treatment described in the present invention is simple in preparation process and steps, high in preparation efficiency, and the solution used is environmentally friendly and non-toxic. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to further understand the present invention, the following drawings are provided for illustration: Figure 1 This is a physical picture of the filler prepared in Example 1 of the present invention.
[0016] Figure 2 This is a detailed view of the filler prepared in Example 1 of the present invention.
[0017] Figure 3 This is a diagram of different contact angles of the AB surface of the filler prepared in Example 1 of the present invention.
[0018] Figure 4 It is the HETP diagram of the filler prepared in Example 1 of the present invention.
[0019] Figure 5 It is the HETP diagram of the filler prepared in Example 2 of the present invention.
[0020] Explanation of reference numerals: θ is the contact angle; HETP is the height of the filler plate; F is the empty tower kinetic energy factor. DETAILED DESCRIPTION
[0021] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. Embodiment 1
[0022] This embodiment provides a high-efficiency composite packing for water treatment, which is made of metal or plastic substrates with different properties on both sides AB to form a structured packing or a random packing. This embodiment preferably uses wire mesh corrugated structured packing, and the specific parameters of the wire mesh corrugated packing are as follows: specific surface area 700m 2 / m 3 , peak height 4.3mm, wave distance 7.1mm, tilt angle 45°, disc height 150mm, diameter 100mm, wire diameter 0.15mm, mesh number 60. The A side adopts metal phosphor bronze wire mesh, and the B side adopts polytetrafluoroethylene.
[0023] The high-efficiency composite filler for water treatment and the preparation method thereof specifically include the following steps: (1) Punch holes in the phosphor bronze wire mesh with a hole diameter of 1 to 8 mm and an opening rate of 1 to 10%.
[0024] (2) The screen produced in step (1) is corrugated with a peak height of 4.3 mm, a wave pitch of 7.1 mm, and an inclination angle of 45°.
[0025] (3) The screen obtained in step (2) is placed in an alkaline degreasing agent mixture and cleaned by ultrasonic cleaning.
[0026] (4) Place the screen obtained in step (3) in deionized water, clean it ultrasonically and dry it.
[0027] (5) A sodium hydroxide and sodium percarbonate mixture aqueous solution is prepared in the treatment tank, the concentration of sodium hydroxide is 3.0 mol / L, and the concentration of sodium percarbonate is 5 mol / L. The solution is circulated internally and the mixed solution is heated to 60° C. The screen of step (4) is placed in the mixed solution and subjected to ultrasonic treatment for 1 hour. During the treatment process, sodium hydroxide and sodium percarbonate are supplemented according to the change in solution concentration.
[0028] (6) Placing the wire mesh treated in step (5) in deionized water, ultrasonically cleaning and drying the wire mesh to form a super-hydrophilic wire mesh.
[0029] (7) Retaining the A side of the screen treated in step (6), spraying polytetrafluoroethylene on the B side to form a hydrophobic layer on the B side.
[0030] (8) Assemble the wire mesh treated in step (7) into a packing with a diameter of 100 mm. Figure 1 For details, see Figure 2 .
[0031] Reference Figure 3 The contact angle of the filler surface A is less than 5°, and the contact angle of the filler surface B is greater than 75°, thereby obtaining a high-efficiency composite filler for water treatment.
[0032] The performance of a high-efficiency composite filler for water treatment prepared in this embodiment is compared with that of a conventional filler. The filler parameters of this embodiment and comparative example 1 are shown in the following table: Embodiment 1 Comparative Example 1 Diameter, mm 100 100 Packing installation height, mm 1500 1500 Plate height, mm 150 150 <![CDATA[Specific surface area, m 2 / m 3 > 700 700 Peak height, mm 4.3 4.3 Wavelength, mm 7.1 7.1 Tilt angle, ° 45 45 Wire diameter, mm 0.15 0.15 Mesh 60 60 Side A Phosphor bronze (prepared according to the method of the present invention) Conventional Phosphor Bronze Side B Polytetrafluoroethylene (prepared according to the method of the present invention) Conventional Phosphor Bronze The difference between the filler in this embodiment and the comparative example 1 is only the different properties of the AB surface described in the present invention.
[0033] A high-efficiency composite filler for water treatment prepared in this embodiment is installed in a tower with a tower diameter of DN100, and the filler installation height is 1.5m. A filler grid is set at the bottom of the filler, and a filler pressure grid and a liquid distributor are set at the top of the filler. A condenser is set at the top of the tower, and a heater is set at the bottom of the tower. The material system operated by the tower is alcohol-water, and the efficiency of the whole tower is tested and compared with the filler of comparative example 1, wherein the structure of the tower is the same during the comparative test, and only the filler is changed.
[0034] Results Figure 4 , F in the figure is the empty tower kinetic energy factor. It can be clearly seen from the figure that the HETP of the high-efficiency composite filler prepared by the method of the present invention is lower than that of the filler in comparative example 1, the efficiency is 25% higher, and its operating flexibility is greater than that of the filler in comparative example 1. Embodiment 2
[0035] This embodiment provides a high-efficiency composite packing for water treatment, which is made of metal or plastic substrates with different properties on both sides AB to form a structured packing or a random packing. This embodiment preferably uses wire mesh corrugated structured packing, and the specific parameters of the wire mesh corrugated packing are as follows: specific surface area 500m 2 / m 3 , peak height 6.2mm, wave distance 10.1mm, tilt angle 30°, disc height 150mm, diameter 600mm, wire diameter 0.12mm, mesh number 60. The A side adopts metal copper wire mesh, and the B side adopts metal stainless steel wire mesh.
[0036] The high-efficiency composite filler for water treatment and the preparation method thereof specifically include the following steps: (1) Flatten and spot weld the copper wire mesh and the stainless steel wire mesh to form a double-layer wire mesh.
[0037] (2) Punch holes in the screen of step (1) with a hole diameter of 1 to 8 mm and an opening rate of 1 to 10%.
[0038] (3) The screen produced in step (2) is corrugated with a peak height of 6.2 mm, a wave pitch of 10.1 mm, and an inclination angle of 30°.
[0039] (4) The screen obtained in step (3) is placed in an alkaline degreasing agent mixture and cleaned by ultrasonic cleaning.
[0040] (5) Place the screen obtained in step (4) in deionized water, clean it ultrasonically and dry it.
[0041] (6) A potassium hydroxide and potassium hypochlorite aqueous solution was prepared in the treatment tank, the concentration of potassium hydroxide was 5.6 mol / L, and the concentration of potassium hypochlorite was 8.3 mol / L. The solution was circulated internally and the mixed solution was heated to 75° C. The screen in step (5) was placed in the mixed solution and ultrasonically treated for 0.45 h. Potassium hydroxide and potassium hypochlorite were supplemented during the treatment process according to the change in solution concentration.
[0042] (7) The wire mesh treated in step (6) is placed in deionized water, ultrasonically cleaned and dried to form a wire mesh having different properties on the AB surface.
[0043] (8) Assemble the wire mesh from step (7) into a packing with a diameter of 600 mm.
[0044] This embodiment produces a high-efficiency composite filler for water treatment, wherein the contact angle of the A surface is less than 5°, and the contact angle of the B surface is greater than 65°.
[0045] The performance of a high-efficiency composite filler for water treatment prepared in this embodiment is compared with that of a conventional filler. The filler parameters of this embodiment and comparative example 2 are shown in the following table: Embodiment 2 Comparative Example 2 (A) Comparative Example 2 (B) Diameter, mm 600 600 600 Packing installation height, mm 2000 2000 2000 Plate height, mm 150 150 150 <![CDATA[Specific surface area, m 2 / m 3 > 500 500 500 Peak height, mm 6.2 6.2 6.2 Wavelength, mm 10.1 10.1 10.1 Tilt angle, ° 30 30 30 Wire diameter, mm 0.12 0.12 0.12 Mesh 60 60 60 Side A Phosphor bronze (prepared according to the method of the present invention) Conventional Phosphor Bronze Conventional stainless steel Side B Stainless steel (produced according to the method of the present invention) Conventional Phosphor Bronze Conventional stainless steel The difference between the fillers in this embodiment and the comparative example 2 is only the different properties of the AB surface described in the present invention.
[0046] A high-efficiency composite filler for water treatment prepared in this embodiment is installed in a tower with a tower diameter of DN600, and the filler installation height is 2.0m. A filler grid is set at the bottom of the filler, and a filler pressure grid and a liquid distributor are set at the top of the filler. A condenser is set at the top of the tower, and a heater is set at the bottom of the tower. The material system operated by the tower is alcohol-water, and the efficiency of the whole tower is tested and compared with the filler of comparative example 2, wherein the structure of the tower is the same during the comparative test, and only the filler is changed.
[0047] Results Figure 5 , F in the figure is the empty tower kinetic energy factor. It can be clearly seen from the figure that the HETP of the high-efficiency composite filler prepared by the method of the present invention is lower than the filler in comparative example 2. The efficiency of the high-efficiency composite filler prepared in this embodiment is 30% higher than that of comparative example 2 (A) and 37% higher than that of comparative example 2 (B), and its operating flexibility is greater than that of the filler in comparative example 2. Embodiment 3
[0048] This embodiment uses the same filler parameters as the first embodiment, except that the A surface uses a metal phosphor bronze mesh and the B surface uses a polytetrafluoroethylene mesh.
[0049] The high-efficiency composite filler for water treatment and the preparation method thereof specifically include the following steps: (1) The phosphor bronze wire mesh and the polytetrafluoroethylene wire mesh are woven together to form a wire mesh having two sides AB.
[0050] (2) Punch holes in the screen of step (1) with a hole diameter of 1 to 8 mm and an opening rate of 1 to 10%.
[0051] (3) The screen produced in step (2) is corrugated with a peak height of 4.3 mm, a wave pitch of 7.1 mm, and an inclination angle of 45°.
[0052] (4) The screen obtained in step (3) is placed in an alkaline degreasing agent mixture and cleaned by ultrasonic cleaning.
[0053] (5) Place the screen obtained in step (4) in deionized water, clean it ultrasonically and dry it.
[0054] (6) A potassium hydroxide and potassium peroxymonosulfonate aqueous solution was prepared in the treatment tank, the concentration of potassium hydroxide was 2.5 mol / L, and the concentration of potassium peroxymonosulfonate was 4.2 mol / L. The solution was circulated internally and the mixed solution was heated to 50° C. The screen of step (5) was placed in the mixed solution and ultrasonically treated for 1.5 hours. Potassium hydroxide and potassium peroxymonosulfonate were supplemented during the treatment process according to the change in solution concentration.
[0055] (7) Place the screen treated in step (6) in deionized water, clean it ultrasonically and dry it.
[0056] (8) Assemble the wire mesh processed in step (7) into filler.
[0057] The high-efficiency composite filler for water treatment prepared in this embodiment has an A surface contact angle of less than 5° and a B surface contact angle of more than 75°, thereby forming a high-efficiency composite filler for water treatment. Embodiment 4
[0058] This embodiment provides a high-efficiency composite packing for water treatment, which is made of a metal or plastic substrate with two sides AB with different properties to form a structured packing or a random packing. In this embodiment, a plate corrugated structured packing is preferred. The A side is made of a metal copper alloy thin plate with a thickness of 0.1 mm, and the B side is made of polypropylene.
[0059] The high-efficiency composite filler for water treatment and the preparation method thereof specifically include the following steps: (1) Punch holes in the copper alloy sheet with a hole diameter of 1 to 8 mm and a porosity of 1 to 10%.
[0060] (2) The copper alloy sheet prepared in step (1) is corrugated by punching.
[0061] (3) The copper alloy sheet obtained in step (2) is placed in an alkaline degreasing agent mixture and cleaned by ultrasonic cleaning.
[0062] (4) The copper alloy sheet obtained in step (3) is placed in deionized water, and is ultrasonically cleaned and dried.
[0063] (5) A mixed aqueous solution of sodium hydroxide, sodium percarbonate and potassium hypochlorite is prepared in a treatment tank, wherein the concentration of sodium hydroxide is 4.5 mol / L, the concentration of sodium percarbonate is 4.5 mol / L, and the concentration of potassium hypochlorite is 3.8 mol / L. The solution is circulated internally and maintained at a room temperature of 25° C. The copper alloy sheet of step (4) is placed in the mixed solution and subjected to ultrasonic treatment for 3 hours. During the treatment process, sodium hydroxide, sodium percarbonate and potassium hypochlorite are supplemented according to the change in solution concentration.
[0064] (6) Placing the copper alloy thin plate treated in step (5) in deionized water, ultrasonically cleaning and drying the plate to form a super hydrophilic thin plate.
[0065] (7) The copper alloy sheet treated in step (6) retains the A side and sprays polypropylene on the B side to form a hydrophobic layer on the B side.
[0066] (8) Assembling the alloy sheets treated in step (7) into a packing.
[0067] The high-efficiency composite plate corrugated packing for water treatment prepared in this embodiment has an A surface contact angle of less than 5° and a B surface contact angle of more than 75°, thereby forming a high-efficiency composite packing for water treatment. Embodiment 5
[0068] This embodiment uses the same copper alloy sheet as the fourth embodiment. The difference is that the filler is a random filler. Specifically, the following steps are included: (1) Spray polypropylene onto the B surface of the copper alloy sheet to form a hydrophobic layer on the B surface.
[0069] (2) The copper alloy sheets prepared in step (1) are made into random packings.
[0070] (3) The random packing of step (2) is placed in an alkaline degreasing agent mixture and cleaned by ultrasonic cleaning.
[0071] (4) The random packing obtained in step (3) is placed in deionized water, cleaned by ultrasonic cleaning and dried.
[0072] (5) A mixture of sodium hydroxide, sodium percarbonate and potassium hypochlorite is prepared in a treatment tank, wherein the concentration of sodium hydroxide is 4.5 mol / L, the concentration of sodium percarbonate is 4.5 mol / L, and the concentration of potassium hypochlorite is 3.8 mol / L. The solution is circulated internally and maintained at a room temperature of 25° C. The random packing of step (4) is placed in the mixed solution and subjected to ultrasonic treatment for 3 hours. During the treatment process, sodium hydroxide, sodium percarbonate and potassium hypochlorite are supplemented according to the change in solution concentration.
[0073] (6) The random packing treated in step (5) is placed in deionized water, cleaned by ultrasonic wave and dried, thereby obtaining a high-efficiency composite random packing having AB different properties for water treatment.
[0074] The above detailed description of the preferred embodiments of the present invention is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.
Claims
1. A high-efficiency composite filler for water treatment, characterized in that: The filler is a composite material composed of two base materials with different properties, forming two sides AB with different properties. The A side has super strong hydrophilicity, and the B side is less hydrophilic than the A side.
2. A high-efficiency composite filler for water treatment according to claim 1, characterized in that: The material of the A side is phosphor bronze, copper, brass or copper alloy; the material of the B side is a metal or plastic of a different type from that of the A side.
3. The high-efficiency composite filler for water treatment according to claim 1, characterized in that: The substrate is a screen, a thin plate, a mesh or a combination thereof; the screen has a wire diameter of 0.005-5 mm and a mesh size of 10-200; the thin plate has a thickness of 0.01-5 mm; and the mesh has a hole diameter of 0.05-20 mm.
4. The high-efficiency composite filler for water treatment according to claim 1, characterized in that: The packing is a structured packing such as a wire mesh corrugated packing, a plate corrugated packing, a wire mesh plate combined corrugated packing, a mesh corrugated packing, or a random packing such as a ball ring, a step ring, a Raschig ring, or a theta ring; the specific surface area of the packing is 50-2000m 2 / m 3 , the porosity is 65~99.5%.
5. A method for preparing a high-efficiency composite filler for water treatment according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step S1: placing the filler in an alkaline degreasing agent mixture and cleaning it by ultrasonic cleaning; Step S2: The filler is placed in deionized water, ultrasonically cleaned and dried; Step S3: preparing an aqueous solution of a mixture of A and B, circulating the solution internally and heating the mixed solution to raise the temperature, and after reaching a certain temperature, placing the filler in the mixed solution and performing ultrasonic treatment; Step S4: The treated filler is placed in deionized water, cleaned by ultrasonic cleaning and dried.
6. The method for preparing a high-efficiency composite filler for water treatment according to claim 5, characterized in that: The substance A is one or more combinations of sodium hydroxide, potassium hydroxide, and lithium hydroxide, and the substance B is one or more combinations of potassium peroxymonosulfonate, sodium percarbonate, potassium percarbonate, potassium hypochlorite, and sodium hypochlorite.
7. The method for preparing a high-efficiency composite filler for water treatment according to claim 5, characterized in that: The concentration of substance A in the mixed solution is 0.5-12 mol / L, and the concentration of substance B is 0.2-16 mol / L.
8. The method for preparing a high-efficiency composite filler for water treatment according to claim 5, characterized in that: The treatment heating temperature is 25-100°C.
9. The method for preparing a high-efficiency composite filler for water treatment according to claim 5, characterized in that: The filler treatment time is 0.5 to 5.0 hours.
Citation Information
Patent Citations
Filler extraction tower for gradient fractionating separation of large phase ratio system, and extraction method thereof
CN102728099A
Composite filler of metallic framework-macromolecular material and production method thereof
CN102941055A
Super-hydrophilic and underwater super-oleophobic oil-water separation mesh membrane having, and its preparation method
CN102974226A
Rotary filling bed based on hydrophilic-hydrophobic combined filler, and system
CN110252238A
Catalytic filler for hydrogen isotope oxide separation and preparation method and application thereof
CN112473692A